Factors Affecting Speaking Anxiety of Thai Students During Oral Presentation: Faculty of Education in TSAI - Muhamad Sofian Hadi; Lidiyatul Izzah; Mareena Masae (English Department, Faculty of Education, Universitas Muhammadiyah Jakarta, 2020)
The objective of this research is to find out the effectiveness to use Foreign Language Classroom Anxiety Questionnaire as a tool that adapted in Speaking skills from first-year until a fourth-year grade of Thai students in TSAI. This study used a Quantitative Method with Survey research by implementing the design of an online questionnaire. In this study, the participants are all Thai students, the Faculty of Education in TSAI who have been studying in Jakarta and west Jawa with 46 Participants. The data were collected by giving Foreign Language Classroom Anxiety Questionnaire as the instruments. The result of significant scores of Thai students after examined the Foreign Language Classroom Anxiety Questionnaire is x 3 556 within the high-anxiety level, it can be said that there are major factors that affecting speaking anxiety during English oral presentation skills of Thai students, the Faculty of Education in TSAI.